Borthwickia W. W. Smith (Capparaceae Juss.) a new genus for the flora of Vietnam - Cuong, Nguyen The; Trai, Ngo Sy; Thuong, Sy Danh (Academia Journal of Biology, 2014)
The genus Borthwickia (Capparaceae) was described and published by W. W. Smith in 1911, with Borthwickia trifoliata W. W. Smith as the unique species. The distribution of this genus has been known in Burma and China (Yunnan). During the study of Capparaceae specimens and documents, we have found that Borthwickia distributed also in Vietnam, with specimens of the species B. trifolia W. W. Smith collected in the Bat Xat district, Lao Cai province. This was a new genus for the flora of Vietnam.